The Long-Term Effects of Pitavastatin on Blood Lipids and Platelet Activation Markers in Stroke Patients: Impact of the Homocysteine Level - Sugimoto, Hideki (PLoS One, 2014)
To examine the impact of the plasma homocysteine level on the anti-atherosclerotic effects of pitavastatin treatment, we retrospectively examined 59 patients who had a history of stroke and had been prescribed pitavastatin for the treatment of dyslipidemia at the Neurology department of Toho University Ohashi Medical Center Hospital. The patients were classified into two groups according to their homocysteine levels. Carotid artery plaque progression was determined before and after pitavastatin treatment. Plasma levels of high-sensitivity C-reactive protein, platelet molecular markers, and von Willebrand factor were measured. Pitavastatin treatment had beneficial effects on the lipid profiles of these patients and slowed atherosclerosis progression. These effects were observed in both the high and low homocysteine groups. Proactive lipid intervention using pitavastatin may inhibit the progression of atherosclerosis and contribute to secondary prevention of stroke in high-risk patients. We conclude that this statin could inhibit progression at any stage of disease and should therefore be proactively administered to these patient groups, regardless of disease severity.